Impaired Endothelial Repair Capacity of Early Endothelial Progenitor Cells in Hypertensive Patients With Primary Hyperaldosteronemia: Role of 5,6,7,8-Tetrahydrobiopterin Oxidation and Endothelial Nitric Oxide Synthase Uncoupling - Chen, Long; Ding, Mei-Lin; Wu, Fang; He, Wen; Li, Jin; Zhang, Xiao-Yu; Xie, Wen-Li; Duan, Sheng-Zhong; Xia, Wen-Hao; Tao, Jun (Hypertension (Dallas, Tex. 1979), 2016)
Although hyperaldosteronemia exerts detrimental impacts on vascular endothelium in addition to elevating blood pressure, the effects and molecular mechanisms of hyperaldosteronemia on early endothelial progenitor cell (EPC)–mediated endothelial repair after arterial damage are yet to be determined. The aim of this study was to investigate the endothelial repair capacity of early EPCs from hypertensive patients with primary hyperaldosteronemia (PHA). In vivo endothelial repair capacity of early EPCs from PHAs (n=20), age- and blood pressure–matched essential hypertension patients (n=20), and age-matched healthy subjects (n=20) was evaluated by transplantation into a nude mouse carotid endothelial denudation model. Endothelial function was evaluated by flow-mediated dilation of brachial artery in human subjects. In vivo endothelial repair capacity of early EPCs and flow-mediated dilation were impaired both in PHAs and in essential hypertension patients when compared with age-matched healthy subjects; however, the early EPC in vivo endothelial repair capacity and flow-mediated dilation of PHAs were impaired more severely than essential hypertension patients. Oral spironolactone improved early EPC in vivo endothelial repair capacity and flow-mediated dilation of PHAs. Increased oxidative stress, oxidative 5,6,7,8-tetrahydrobiopterin degradation, endothelial nitric oxide synthase uncoupling and decreased nitric oxide production were found in early EPCs from PHAs. Nicotinamide adenine dinucleotide phosphate oxidase subunit p47 phox knockdown or 5,6,7,8-tetrahydrobiopterin supplementation attenuated endothelial nitric oxide synthase uncoupling and enhanced in vivo endothelial repair capacity of early EPCs from PHAs. In conclusion, PHAs exhibited more impaired endothelial repair capacity of early EPCs than did essential hypertension patients independent of blood pressure, which was associated with mineralocorticoid receptor–dependent oxidative stress and subsequently 5,6,7,8-tetrahydrobiopterin degradation and endothelial nitric oxide synthase uncoupling.